(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The article states about the social reformer,grant humanist and pioneer of Indian renaissance Ayya Vaikundar. His famousslogan was “ONE CASTE, ONE RELIGION, ONE CLAN, ONE WORLD, ONE GOD”which makes all caste people to feel equality, he spread Ayya cult with his disciples. His main disciples are Dharma cheedar, Bheeman cheedar, Arjunan cheedar, Nakulan cheedar, Sahadevan cheedar. Ayya started Annadhanam which is the important dharma. As he told he attain nirvana on 2ndJune 1891,many prophecies of Ayya became reality. The divine words of Ayya make the downtrodden people to have an independent and fearless life, a lotus carrying a flame is the symbol of Ayya vazhi,the detailed work of Ayya Vaikundar is stated in this article.